Analyzing the Impact of Blockchain Technology on Transaction Security with a Bibliometric Perspective - Judijanto, Loso; Gamaliel, Fritz (Eastasouth Institute, 2024)
This study presents a comprehensive bibliometric analysis aimed at assessing the impact of blockchain technology on transaction security. Spanning the period from 2016 to 2024, our analysis encompasses a total of 980 papers, revealing a profound scholarly interest and a rapidly evolving research landscape in this domain. Through quantitative metrics such as citation analysis, and qualitative insights from thematic, overlay, density, and author network visualizations, we delineate the key trends, challenges, and future directions in blockchain research. The findings indicate a marked emphasis on the decentralization, security, and transparency that blockchain offers, with significant applications across banking, energy trading, the Internet of Things (IoT), healthcare, and education sectors. Despite its promise, the study also identifies persistent challenges related to scalability, interoperability, privacy, and regulatory compliance that need addressing. By mapping the scholarly landscape, this research not only sheds light on the current state of blockchain technology in enhancing transaction security but also outlines potential avenues for future research, underscoring the technology's interdisciplinary impact and its evolving role in digital transactions.